Incidence and Risk Factors of Iatrogenic Retinal Breaks: 20-Gauge versus 25-Gauge Vitrectomy for Idiopathic Macular Hole Repair - Norio Fujiwara; Goji Tomita; Fumihiko Yagi (Journal of Ophthalmology)
Purpose. We compared the incidences of iatrogenic retinal breaks and postoperative retinal detachment between eyes that underwent 20-gauge vitrectomy and those that underwent 25-gauge vitrectomy for idiopathic macular hole repair. Methods. This retrospective nonrandomized consecutive observational case series included 185 eyes of 183 patients (130 eyes of 129 patients and 55 eyes of 54 patients in the 20- and 25-gauge groups, respectively). We assessed the relationship between the incidence of retinal breaks and postoperative retinal detachment and related this to posterior vitreous detachment and lattice degeneration. Results. The incidences of iatrogenic retinal breaks were 36.9% and 12.7% in the 20-gauge and 25-gauge groups, respectively. These groups did not differ in their respective frequencies of posterior vitreous detachment (the 20-gauge group: 31.5% and the 25-gauge group: 27.3%) and lattice degeneration (the 20-gauge group: 14.6% and the 25-gauge group: 7.3%). Among eyes without lattice degeneration, the 20-gauge group showed a higher incidence of iatrogenic retinal breaks than the 25-gauge group. However, among the eyes with lattice degeneration, the frequency of retinal breaks did not differ between the two surgery types, and four cases of postoperative retinal detachment were reported in both groups. Conclusions. The incidence of retinal breaks related to idiopathic macular hole surgery is higher among patients undergoing 20-gauge vitrectomy than among those undergoing 25-gauge vitrectomy. Posterior vitreous detachment and lattice degeneration are associated with considerably increased incidences of retinal break.